Family book, ancestral cell: skete technologies of self-preservation in the period of urbanization - Dutchak, Elena E. (The New Research of Tuva, 2025)
The article analyzes the adaptation strategies of Siberian Old Believers of the Chapel and Wanderer confessions to intraregional migrations of the 1950s–1980s. Using the example of communities located in rural areas of the Republic of Tuva and the Tomsk Region, the author examines the technologies of solidarity within a religious collective that was differentiated by age and spatially dispersed between the taiga skete, the village, and the town, and he models the processes of prolonging monastic principles within the structure of family values.The methodological framework of the study includes a) the concept of lived religion, which focuses on every day, fluid states of confessional identity; and b) the analytical program of the material turn, which highlights the influence of material worlds on the social, intellectual, and emotional activity of individuals and groups. The source base consists of Old Believer hagiographic, memoir, and genealogical narratives; journalistic and administrative materials; ownership notes in books; and field interviews conducted by researchers.The study aims to test the hypothesis that the inheritance of family property associated with religious ideas serves as a tool for the intergenerational transmission of the hermitic tradition. It has been revealed that the emergence of family cells and taiga settlements determined the historical features of Old Believer resettlement in the taiga zone and the interdependence of monastic and peasant households. The article describes the practices of involving laypeople in operations with liturgical and doctrinal books and characterizes the results of their use in maintaining “old” skete dynasties, creating “new” ones, and expanding resources for the formation of “future” ones.An analysis of the network relations of the skete with its near and distant environment, with both “own” and “others,” demonstrated that the reproduction of monastic institutions under conditions of youth outmigration and socio-ideological transformations is based on the delegation to the skete of the function of custodian of family “places of salvation” and keeper of family “prayed-over” books.
Keywords: Old Believer skete; Chapel confession; Wanderer confession; Ob-Yenisei region; Tuva; Tomsk Region; monasticism; religious upbringing; Christian book; Cyrillic tradition